Structural basis for the transition from translation initiation to elongation by an 80S-eIF5B complex - Jinfan Wang (Nature Portfolio, 2020)
The GTPase eIF5B is involved in the correct positioning of the initiator Met-tRNAi Me t on the ribosome during the late stages of translation initiation. Here the authors present a cryo-EM structure of the ribosome in complex with eIF5B and Met-tRNAi Met immediately before transition into elongation, providing insight on Met-tRNAi Metdelivery and how the correct reading frame is established.